First-principles calculations on the mechanical, electronic and thermodynamic properties of t-C88 carbon allotrope under high pressure - Arjun, P.; Nagarajan, V.; Chandiramouli, R. (Physica. B, Condensed matter, 2025)
The new tetragonal carbon allotrope t-C88, which is the subject of this work, is distinguished by its distinct mechanical performance at high pressure and structural characteristics. t-C88 shows hybridization of sp2 and sp3 carbon atoms, in contrast to other carbon compounds that are mostly made of sp2-hybridized carbon atoms. We investigated the elastic characteristics and anisotropy of t-C88 at different pressures (0–20 GPa) using first-principles computations. Our results show that t-C88 exhibits strong elastic anisotropy, especially above 15 GPa, and retains mechanical stability by meeting Born-Huang requirements. In order to emphasize the material's reaction to high pressure, this study offers a wealth of information on the following criteria: Poisson's ratio (v), bulk modulus (B), shear modulus (G), Young's modulus (E), elastic constants (Cij), and universal anisotropy (AU). Interestingly, t-C88 shows more resistance to compressional deformation than shear deformation. The high B/G ratio of t-C88 indicates that its mechanical characteristics indicate that it will become ductile with increasing pressure. Moreover, the understanding of t-C88 under high-pressure conditions will open viable options for various applications, including high-performance composites for enhanced strength and durability, protective coatings requiring superior mechanical stability, advanced sensors due to its tuneable electronic properties, energy storage devices leveraging its unique characteristics, and electronic components. [Display omitted]